Peran Manajemen Pendidikan dalam Mendorong Interaksi Sosial Yang Efektif di Kelas Kolaboratif - Lathifah Hanum, Mutiara; Qotrunada Fadhilah, Rahmatunnisa; Nisa Fauziah, Rosa; Permana, Hinggil (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
Social interaction among students in collaborative classroom learning is a key factor in creating an effective learning process. This study aims to identify patterns of social interaction among students, understand group dynamics, and evaluate the impact of those interactions on the learning process. Phenomena such as the dominance of certain students, low active participation, and exclusivity of social groups often hinder the formation of healthy interactions. This study employs a qualitative approach using descriptive observation methods. Data was collected through direct observations, interviews with teachers and students, and document analysis. The research results show that trust among students, teachers' communication styles, and the design of the learning environment significantly affect the quality of social interactions in the classroom. These findings have important implications for the development of more inclusive, participatory, and student-centered learning strategies that enhance students' social skills.